Perceptions of small producers about changes in climate and their effect on milk production systems - Navas Panadero, Alexander (2022)
The aim of this study was to know the perception and knowledge of small producers about the behavior of the climate, its effect on milk production and the practices that allow adaptation to this behavior. The study was developed in Carmen de Carupa and Suesca (Cundinamarca, Colombia) with 40 producers who shared their knowledge through a semi-structured interview. The causes of climate change, events that affect milk production, changes in the climate in recent years and strategies that allow its adaptation were investigated. The humidity temperature index, precipitation, milk production and forage quality were determined. Frequency and principal component analysis were analysed through the Infostat® program. Producers considered deforestation as the main cause of climate change, perceived changes in climate and recognized droughts, frosts and high temperatures as events with the greatest negative impact on milk production, perceived changes in rainy seasons and less precipitation, longer droughts, increase in temperature and frosts during the year. They also considered agroecological practices important to adapt to climate variability. Milk production presented a positive relationship with digestibility and crude protein, a negative relationship with neutral detergent fibre and acid detergent fibre, as well as between precipitation with dry matter and milk production, which corresponded to some of the producers’ perceptions. It is concluded that small milk producers have perceptions and knowledge of climate changes, its impact on milk production and practices that allow adaptation to conditions of seasonality and climate variability.